The Impact Of Effleurage Massage On Postpartum Women In The Mother's Care Unit At SMC Hospital's Afterpains Pain - Eka Frenty Hadiningsih (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
Background: Physiological and psychological changes in postpartum mothers are common. One such change is the body's response to uterine contractions known as afterpains, which last for two to four days after delivery and cause pain that can occasionally interfere with activities. Effleurage massage is one type of non-pharmacological therapy that may be used to treat pain since it is a painful sensory and emotional experience that needs both treatment and medication. The goal is to find out in 2020 how effleurage massage affects postpartum moms' after-pain in the nursing room at SMC Samarinda Hospital. Research Methods: This study employed a quantitative pre-experimental pretest-posttest design with a single set of participants. With a total of 35 respondents, the sampling method employed purposive sampling. The research instrument used a questionnaire sheet for the Numeric Rating Scale (NRS) pain scale. Results: the study using the Wilcoxon statistical test obtained ρ.value = 0,000 <α = 0.05, Conclusion: there is an effect of effleurage massage on afterpains in postpartum mothers. To overcome afterpains pain, it is hoped that midwives can provide loving care for mothers in pain management, one of which is effleurage massage